2015
DOI: 10.1155/2015/502454
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Pharmacological Activity ofCymbopogon winterianusJowitt ex Bor (Poaceae) Leaf Essential Oil ofβ-Cyclodextrin Inclusion Complexes

Abstract: This study aimed to evaluate the orofacial antinociceptive effect of the Cymbopogon winterianus essential oil (LEO) complexed in β-cyclodextrin (LEO-CD) and to assess the possible involvement of the central nervous system (CNS). The LEO was extracted, chromatographed, and complexed in β-cyclodextrin. The complex was characterized by differential scanning calorimetry (DSC) and thermogravimetry derivative (TG/DTG). Male Swiss mice (2-3 months) were treated with LEO-CD (50–200 mg/kg, p.o.), vehicle (distilled wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…C. jwarancusa was found to have a flukicidal activity which used as alternative sources of treatment for trematodes infection (Shafiq et al 2015). C. validus (Stapf) Stapf ex Burtt Davy had potential as an anti-inflammatory (Rungqu et al 2016), and C. winterianus was found exhibiting potential as a mosquito repellent, bioinsecticide (Deletre et al 2015;Sajo et al 2015;Silva et al 2018), and as an orofacial antinociceptive (Santos et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…C. jwarancusa was found to have a flukicidal activity which used as alternative sources of treatment for trematodes infection (Shafiq et al 2015). C. validus (Stapf) Stapf ex Burtt Davy had potential as an anti-inflammatory (Rungqu et al 2016), and C. winterianus was found exhibiting potential as a mosquito repellent, bioinsecticide (Deletre et al 2015;Sajo et al 2015;Silva et al 2018), and as an orofacial antinociceptive (Santos et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Complexation of oils with CDs is frequently found in the literature. Some examples are the complexation of the essential oil of Citrus sinensis (L.) Osbeck with β-CD [ 21 ], the leaf essential oil of Cymbopogon winterianus Jowitt ex Bor (Poaceae) with β-CD [ 22 ], the leaf essential oil of Lippia grata with β-CD [ 23 ] and the leaf essential oil of Ocimum basilicum with β-CD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Union of Pure and Applied Chemistry (IUPAC), numerous drugs of clinical importance have β-cyclodextrins (βCD) present in their composition, such as the cephalosporin, piroxicam and tiaprofenic acid (Szejtli, 2005). Recently, our research group has focused on the complexation of NP, mainly non-polar compounds such as terpenoids, with βCD (Nascimento et al, 2015;QuintansJúnior et al, 2013;Santos et al, 2015;Siqueira-Lima et al, 2014), and we have reported that this complexation was able to improve the effect of these substances mainly for FM or CMP approaches (Nascimento et al, 2014;. Moreover, preclinical and clinical evidence have demonstrated that the complexation in CDs is capable to improve pharmacological effect of analgesic and anti-inflammatory drugs Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%